The Effect of Board Gender Diversity on Corporate Sustainability Performance with Enterprise Risk Management as a Moderating Variable - Nurul Hidayah; Lucky Nugroho; Rimi Guslinana Mais (International Journal of Social Science and Business, 2023)
Corporate Sustainability Performance is an approach taken by companies to create long-term profits by developing business strategies that prioritize profits and pay attention to social, cultural, economic, and environmental factors. Gender diversity plays an important role in achieving sustainable performance because the gender diversity of board members can improve company performance. This study aims to examine the effect of board gender diversity on corporate sustainability performance by using ERM as a moderation variable. The study in this study took samples of energy and mining companies on the IDX. This includes mining companies that have published integrated reports (IRs). The type of data used is secondary data using random sampling to determine the number of sampling trials. This study used qualitative descriptive approach and causality method. Data analysis in this study used SPSS to examine the effect of the independent variable on the dependent variable. The results of this study provide an in-depth understanding of the relationship between independent and dependent variables, with implications that can increase awareness of the importance of gender diversity in the context of sustainable company performance.